X-ray fluorescence spectroscopy (XRF) applied to plant science: Challenges towards: In vivo analysis of plants - Montanha, Gabriel Sgarbiero; Rodrigues, Eduardo Santos; Marques, Joaõ Paulo Rodrigues; De Almeida, Eduardo; Dos Reis, André Rodrigues [UNESP]; Pereira De Carvalho, Hudson Wallace (Oxford University Press (OUP), 2020)
X-ray fluorescence spectroscopy (XRF) is an analytical tool used to determine the elemental composition in a myriad of sample matrices. Due to the XRF non-destructive feature, this technique may allow time-resolved plant tissue analyses under in vivo conditions, and additionally, the combination with other non-destructive techniques. In this study, we employed handheld and benchtop XRF to evaluate the elemental distribution changes in living plant tissues exposed to X-rays, as well as real-time uptake kinetics of Zn(aq) and Mn(aq) in soybean (Glycine max (L.) Merrill) stem and leaves, for 48 hours, combined with transpiration rate assessment on leaves by an infrared gas analyzer (IRGA). We found higher Zn content than Mn in stems. The latter micronutrient, in turn, presented higher concentration in leaf veins. Besides, both micronutrients were more concentrated in the first trifolium (i.e., youngest leaf) of soybean plants. Moreover, the transpiration rate was more influenced by circadian cycles than Zn and Mn uptake. Thus, XRF represents a convenient tool for in vivo nutritional studies in plants, and it can be coupled successfully to other analytical techniques.